Vegan tacos : authentic & inspired recipes for Mexico's favorite street food - Wyrick, Jason (Vegan Heritage Press, 2014)
"Celebrated chef Jason Wyrick showcases the liveliness of Mexican flavors and textures with recipes for traditional and creative tacos you can make at home, featuring your own homemade tortillas, salsas, and condiments. These recipes, based on genuine recipes gathered across Mexico, allow you to make authentic tacos using plant-based ingredients. The long-time publisher of The Vegan Culinary Experience points the way to making your own taco components from scratch, while also providing options to substitute store-bought ingredients"--